The naïve language expert: How infants discover units and regularities in speech - Jutta L Mueller (Frontiers Research Topics, 2015)
The advent of behavior-independent measures of cognition and major progress in experimental designs have led to substantial advances in the investigation of infant language learning mechanisms. Research in the last two decades has shown that infants are very efficient users of perceptual and statistical cues in order to extract linguistic units and regular patterns from the speech input. This has lent support for learning-based accounts of language acquisition that challenge traditional nativist views. Still, there are many open questions with respect to when and how specific patterns can be learned and the relevance of different types of input cues. For example, first steps have been made to identify the neural mechanisms supporting on-line extraction of words and statistical regularities from speech. Here, the temporal cortex seems to be a major player. How this region works in concert with other brain areas in order to detect and store new linguistic units is a question of broad interest. In this Research Topic of Frontiers in Language Sciences, we bring together experimental and review papers across linguistic domains, ranging from phonology to syntax that address on-line language learning in infancy. Specifically, we focused on papers that explore one of the following or related questions: How and when do infants start to segment linguistic units from the speech input and discover the regularities according to which they are related to each other? What is the role of different linguistic cues during these acquisition stages and how do different kinds of information interact? How are these processes reflected in children's behavior, how are they represented in the brain and how do they unfold in time? What are the characteristics of the acquired representations as they are established, consolidated and stored in long-term memory? By bringing together behavioral and neurophysiological evidence on language learning mechanisms, we aim to contribute to a more complete picture of the expeditious and highly efficient early stages of language acquisition and their neural implementation.